RehabVisual: Adapting and Testing the Visuomotor Skills Stimulation Platform on Patients with Multiple Sclerosis - Henriques, Margarida Lourenço (2023)
Multiple Sclerosis (MS) is the most prevalent immune-mediated inflammatory demyeli- nating disease, affecting the Central Nervous System (CNS). Although the incidence and prevalence of this condition can be difficult to quantify accurately, it is estimated that 2.8 million people globally suffer from this pathology. While MS patients may experience a variety of neurological symptoms depending on the locations of the lesions in the CNS, visual impairments are among the most common ones. However, conventional methods used in both assessment and rehabilitation of the visuomotor competences are not sufficient to deliver objective assessments, nor therapies tailored to the patient’s needs. In this sense, the present dissertation emerged, with the objective of adapting and testing the usability of the RehabVisual platform in MS patients. This platform was developed as part of previous master’s dissertations, serving as a tool for conducting objective and standardized assessments of visuomotor skills and aiming to provide a specific monitoring and clinical intervention. This result is obtained through the utilization of an eye tracking system, implemented to integrate the platform. Before applying RehabVisual in a clinical context, a normative base was established using 50 healthy individuals for later comparison. The experimental group consisted of 25 individuals diagnosed with MS, with and without confirmed visuomotor alterations. The protocol, identical for both groups, involved watching three videos, each with a visual stimulus describing a different path. By recording the individuals while they watched the videos, it was possible to calculate the Mean Euclidean Distance between the gaze and stimulus positions for each video and each participant, using the mentioned eye tracking system. This allowed assessing the patients’ performance in tracking the stimulus, evaluating their visuomotor competencies. The results obtained demonstrated that this platform had a promising performance in the assessment of visuomotor alterations, as well as in their quantification, representing a potential auxiliary tool for the healthcare professionals.